Development of a scale measuring online sexual harassment: Examining gender differences and the emotional impact of sexual harassment victimization online - Buchanan, Niall (Legal and criminological psychology, 2022)
Purpose This study aimed to outline the construct of online sexual harassment (OSH) to ensure its accurate measurement and to develop a tool to measure OSH victimization in adults. Secondary aims were to explore potential gender differences in victimization and the emotional impact of OSH. Methods A systematic process was used to develop The Online Sexual Harassment Scale (OSHS) to measure OSH victimization. This included a systematic review of current literature, content analysis of online posts from the Everyday Sexism Website, exploratory factor analysis of a pilot scale, then a subsequent confirmatory factor analysis to confirm scale items, structure and ensure scale reliability. Finally, an online survey using the OSHS explored the emotional impact of OSH. Results Two types of OSH, gender harassment and unwanted sexual attention were identified. The OSHS reliably measured both types of harassment, ω = .95. The most frequent type of OSH found for male and female participants was unwanted sexual attention. Univariate analysis found that females (M = 0.83) experienced significantly higher levels of OSH than males (M = 0.56). Further analysis found that the emotional impact of OSH was significantly more upsetting for females for both types of OSH. Conclusions This study contributes a valid a reliable way to measure OSH in adult victims. The development of the OSHS would benefit from further testing using a larger and more diverse sample, which should include non-student populations.